Diagnostic Value of Platelet Indices in Patients with Pulmonary Embolism - Andi Handayani Tanra; Lopa AT; Esa T; Rauf DE (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Pulmonary embolism is caused by a thrombus that blocks the pulmonary artery. The role of the platelet is mainly relatedto the formation of thrombus. This study aimed to determine the diagnostic value of platelet indices in patients withpulmonary embolism. This study was a retrospective observational research involving 55 patients with and withoutpulmonary embolism at the period of January 2014 and June 2019 at Dr. Wahidin Sudirohusodo Central Hospital, Makassar.The diagnosis of pulmonary embolism was based on CT angiography. Platelet Indices (PI), Mean Platelet Volume (MPV),Platelet Distribution Width (PDW), and plateletcrit (Pct) were analyzed respectively in two groups. Thirty-one (56.3%)patients were diagnosed with pulmonary embolism. There was significant difference of MPV and Pct values betweenembolism and non-embolism group (9.3±1.5 fL vs. 9.5±0.7 fL, p=0.49) and (0.2±0.1% vs. 0.2±0.1%, p=0.82). Contrastingly,there was a significant difference in PDW value between the two groups (13.2±4.9 fL vs. 9.9±1.1 fL, p=0.002). ReceiverOperating Characteristics (ROC) analysis showed cut-off value ≥ 10.5 fL of PDW with a sensitivity of 77.4%, a specificity of75%, Positive Predictive Value (PPV) of 80%, and Negative Predictive Value (NPV) of 72%. Platelet indices (PDW) showed agood diagnostic value on pulmonary embolism disease with a cut-off value ≥ of 10.5fL.